Magnetically driven hydrogel microrobots for enhancing the therapeutic effect of anlotinib on osteosarcoma - Wang, Haoyu; Jiang, Haitian; Tao, Yining; Yang, Binghui; Shen, Jiakang; Mu, Haoran; Wang, Chongren; Yang, Xiyu; Cai, Zhengdong; Li, Mu; Sun, Wei; Yang, Liu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Osteosarcoma, characterized by high mortality and disability rates, poses a significant challenge due to its complex genetic background and the absence of specific membrane receptors, which hinder effective targeted therapy. Active targeting has emerged as a promising approach to address this issue. Methods In this study, magnetically driven hydrogel robots (MMHR) were utilized to load and deliver drugs precisely to target sites. The drugs included SCR1481B16, a specific MET inhibitor proven to inhibit MET-driven tumor growth, and Anlotinib. The microrobots were designed to navigate under magnetic guidance, enhancing drug efficacy while minimizing damage to normal tissues. Results The study explored the potential of MMHR loaded with SCR1481B16 and Anlotinib in the treatment of Anlotinib-resistant osteosarcoma. The microrobots were successfully designed and produced, demonstrating the ability to deliver drugs precisely to tumor sites. Evaluation of the microrobots showed an enhanced sensitivity of tumors to Anlotinib, providing new insights into the treatment of drug-resistant osteosarcoma. Discussion Tumors overexpressing MET often develop resistance to VEGFR-targeted drugs. The use of SCR1481B16 as a MET inhibitor in combination with Anlotinib, delivered by magnetically driven hydrogel microrobots, offers a novel strategy to overcome this resistance. However, further in-depth research and validation are required before the clinical application of this method can be considered. Conclusion In conclusion, magnetically driven hydrogel microrobots loaded with SCR1481B16 provide a promising new strategy for enhancing the sensitivity of Anlotinib-resistant osteosarcoma, bringing hope for future clinical applications in the treatment of this challenging disease.